1987
DOI: 10.1007/bf01885120
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic lesions and transfascial perirenal spread: Computed tomographic demonstration

Abstract: Computed tomographic (CT) findings in 105 cases of pancreatitis and 107 cases of pancreatic carcinoma were analyzed retrospectively to determine the occurrence and roentgenologic signs of penetration of the anterior renal fascial planes in relation to clinical symptoms. In pancreatitis, the perirenal fat was infiltrated in 7% to variable extents by extrapancreatic fluid collections, either as asymptomatic fluid lying alongside renal fascial planes and perirenal septa (5 cases) or as well-circumscribed fluid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Pancreatic pseudocyst extending into perinephric space has been rarely reported, in ~ 0.9-1.25% of patients with pancreatitis [8]. Kashima et al reported a case of pancreatic pseudocyst penetrating into left renal subcapsular region with pancreatic ductal communication [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic pseudocyst extending into perinephric space has been rarely reported, in ~ 0.9-1.25% of patients with pancreatitis [8]. Kashima et al reported a case of pancreatic pseudocyst penetrating into left renal subcapsular region with pancreatic ductal communication [9].…”
Section: Discussionmentioning
confidence: 99%
“…Digestion of perirenal fat and renal fascia due to seepage of the autolytic enzymes from the inflamed pancreas precedes renal pseudocyst formation [8]. Left kidney is more prone to experience perirenal pseudocysts due to its close anatomic relation with pancreas, whereas on right side, duodenum acts as a barrier [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Michiel et al described well circumscribed perirenal fluid collections in only 2 of the 105 cases of pancreatitis that were evaluated by CT 6. Pseudocysts affecting the kidneys are more common on the left1 since the left kidney shares a close anatomic relation with the pancreas; the duodenum being an anatomical barrier for the spread to the right side 5.…”
Section: Discussionmentioning
confidence: 99%